Palau : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
This paper provides a review of recent economic developments in Palau, covering the first five years of the Compact of Free Association (Compact) with the United States. The paper analyzes the economic growth, prices, wages, and employment. The study assesses the public finances and overall developments, which include revenues and grants, expenditure, local governments, trust funds, and nonfinancial public enterprises. The paper provides a detailed study of the financial and external sectors, current and capital accounts, external debt, and exchange and trade systems.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet